2019
DOI: 10.3847/1538-4357/ab12da
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Efficiency of Converting Magnetar Spindown Energy into Gamma-Ray Burst X-Ray Afterglow Emission and Its Possible Implications

Abstract: Plateaus are common in X-ray afterglows of gamma-ray bursts. Among a few scenarios for the origin of them, the leading one is that there exists a magnetar inside and persistently injects its spin-down energy into an afterglow. In previous studies, the radiation efficiency of this process is assumed to be a constant 0.1, which is quite simple and strong. In this work we obtain the efficiency from a physical point of view and find that this efficiency strongly depends on the injected luminosity. One implication … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 58 publications
1
27
1
Order By: Relevance
“…In this work, we have focussed on the simple case of a precessing dipole. A more thorough analysis would include additional terms in (2) from neutrino-driven mass losses (Thompson, Chang & Quataert 2004), gravitational radiation (Lasky & Glampedakis 2016), multipolar magnetic fields (Mastrano, Suvorov & Melatos 2015), and possible fall-back accretion (Melatos & Priymak 2014), all of which would modify the braking index n of the neutron star and help explain the inferred values 3 n 5 for various GRB remnants (Xiao & Dai 2019;Lü, Lan & Liang 2019). In a plasma-filled magnetosphere, the braking index reads n ≈ 3 + 2 sin 2 α cos 2 α 1 + sin 2 α −2 (Arzamasskiy, Philippov & Tchekhovskoy 2015), which is generally greater than 3 though fluctuates as α wobbles in a precessing model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we have focussed on the simple case of a precessing dipole. A more thorough analysis would include additional terms in (2) from neutrino-driven mass losses (Thompson, Chang & Quataert 2004), gravitational radiation (Lasky & Glampedakis 2016), multipolar magnetic fields (Mastrano, Suvorov & Melatos 2015), and possible fall-back accretion (Melatos & Priymak 2014), all of which would modify the braking index n of the neutron star and help explain the inferred values 3 n 5 for various GRB remnants (Xiao & Dai 2019;Lü, Lan & Liang 2019). In a plasma-filled magnetosphere, the braking index reads n ≈ 3 + 2 sin 2 α cos 2 α 1 + sin 2 α −2 (Arzamasskiy, Philippov & Tchekhovskoy 2015), which is generally greater than 3 though fluctuates as α wobbles in a precessing model.…”
Section: Discussionmentioning
confidence: 99%
“…where η ≤ 1 is an efficiency parameter accounting for imperfect conversion [see e.g. Xiao & Dai (2019)]. If the newborn star is an oblique rotator with millisecond period and strong ( 10 15 G) magnetic field, the dominant term within L may be sourced by electromagnetic braking.…”
Section: Millisecond Magnetar Engines For Grbsmentioning
confidence: 99%
“…We place a set of initial values to minimize the function with the iminuit interface and the migrad optimizer. We assume a fallback mass of M fb = 0.8 M e (Metzger et al 2018) and η x = 0.1 (Bernardini et al 2013;Xiao & Dai 2019). We report the best-fit values of the magnetic field, spin period, and fallback timescale in Table 7.…”
Section: Modeling the Multiwavelength Light Curvesmentioning
confidence: 99%
“…The alignment and magnetic dipole moment decline of a newborn magnetar in the early stage may result in the braking index evolution, and its value can be greater than 3 (S ¸aşmaz Muş et al 2019). The n value may also be slightly greater than 3 when the radiation efficiency decreases with time (Xiao & Dai 2019). Alternately, Metzger et al (2018) suggested that the fall-back accretion may lead to n < 3.…”
Section: Braking Indexmentioning
confidence: 99%
“…The radiation efficiency is quite uncertain. Xiao & Dai (2019) showed η as a function of L k for different bulk saturation Lorentz factors (Γ sat ) of the DR wind. The efficiency dramatically increases with the decrease of the Γ sat value.…”
Section: Initial Spin Period and Magnetic Field Strengthmentioning
confidence: 99%